A gestão dos resíduos eletroeletrônicos nas IFES: uma análise do plano de gestão de logística sustentável das universidades federais do Nordeste brasileiro - Silva, Brisa Kelly Oliveira Lopes da (Universidade Federal Rural do Semi-Árido, 2018)
of waste electrical and electronic equipment (WEEE) in federal institutions of high education (IFES). The main objective is to analyze the named Sustainable Logistics Management Plans (PLS) of the federal universities located in the Brazilian northeast, with the main focus the management of electrical and electronic waste. The research method used in this study involved the documentary analysis of the PLS of the federal universities located in the Brazilian northeast, considering the universe of this research only the institutions that had PLS published on the institutional website. Finally, was used as a data collect instrument a checklist with information about the compliance with the IN nº 10/2012 and about the management of electrical and electronic waste. The main results of this study demonstrated that just one university published its PLS in the term according to the IN nº 10/2012; none have all PLS reports of each year since their publication; all the institutions meet the minimum requirements regulated by the IN nº 10/2012 and, of the 10 universities analyzed, five present some action or proposal about the management of WEEE, mainly the collection of stacks and batteries. The results also demonstrates that nine institutions didn’t present in PLS information about the amount of WEEE generated. In this sense, the study concludes that the institutions still deal with the management of waste electrical and electronic equipment in a superficial way, presenting punctual actions, mostly limited to the collection of stacks and batteries, and the PLS demonstrates an absence of control and/or knowledge about the amount of WEEE generated.
Monografia
Keywords: Resíduos de equipamentos eletroeletrônicos; Gestão dos resíduos eletroeletrônicos; Resíduos de Equipamentos ElPlano de gestão de logística sustentável; Universidades Federais; Waste electrical and electronic equipment.; Management of waste electrical and electronic equipment; Sustainable logistics management plan; Federal universities; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO